1903 Mont. Laws 135-36 - (:unkn) unknown (My University, 1903)
An Act to Amend Section 908 of Chapter I Title VIII Part IV Division I of the Civil Code of Montana, and to Repeal Section 689 of the Penal Code, ch. 66, § 1: If any railroad corporation within this State shall . . . transport within this State on any of its passenger cars, any oil of vitrol, gun powder, Lucifer matches, nitro glycerine, glynon oil, nytroleum or blasting oil, or nitrates oil, or powder mixed with any such oil, or fiber saturated therewith, or duolin or giant powder, or blasting powder, or any other goods in a dangerous nature . . . shall be deemed guilty of a misdemeanor,
Keywords: GUNPOWDER - TRANSPORTATION